Foodborne and neglected parasitic zoonoses in Ethiopian red meat animals: insights from a systematic review and meta-analysis - Fenta, Melkie Dagnaw; Eshetu, Biruk; Bitew, Abebe Belete; Dejene, Haileyesus; Kinde, Mebrie Zemene (Frontiers in Veterinary Science, 2025)
BackgroundThe most prevalent yet neglected cestode meat-borne parasitic zoonoses are bovine cysticercosis and cystic echinococcosis, while the most common meat-borne protozoan zoonoses are toxoplasmosis and cryptosporidiosis in Ethiopia. In Ethiopia, bovine cysticercosis, cystic echinococcosis, toxoplasmosis, and cryptosporidiosis are the most common but neglected meat-borne parasites. The main transmission route is through contaminated meat products. The aim of this review was to provide an overall prevalence estimation of major food-borne zoonotic parasitic in ruminants in Ethiopia.MethodsThe present meta-analysis was conducted based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Articles were searched in PubMed, Google Scholar, Web of Science, and HINARI. A total of 104 eligible articles were included in the final meta-analysis. The pooled prevalence estimates and 95% confidence intervals (CI) were conducted using random effect model, and heterogeneity was assessed using I2 statistics.ResultsToxoplasmosis had the highest pooled prevalence (38, 95% CI: 30–46%), followed by cystic echinococcosis (25, 95% CI: 18–32%), cryptosporidiosis (14, 95% CI: 9–19%), and bovine cysticercosis (9, 95% CI: 5–13%). In most individual analyses, Egger’s regression test did not reveal significant publication bias, since the p-values were greater than 0.05. Regional subanalysis showed that bovine cysticercosis was most prevalent in the Amhara region (16, 95% CI: 6–13%), whereas cystic echinococcosis was highest in Oromia (33, 95% CI: 22–45%) and Tigray (29, 95% CI: 24–33%). Host-wise analysis indicated that toxoplasmosis was most prevalent in sheep (41%), followed by goats (39%), and cattle (28%). Cryptosporidiosis was most commonly detected in cattle (16%), sheep (11%), and goat (8%). Age-based analysis revealed a higher prevalence in calves and lambs with an estimated pooled prevalence of 15% (I2 = 83%).ConclusionThe increasing prevalence of meat-borne parasitic zoonoses in Ethiopia highlights the need for urgent intervention. Strengthening disease surveillance, enforcing strict meat inspection protocols, and raising public awareness about zoonotic risks are critical for effective control. A coordinated approach between veterinary professionals, public health authorities, and policymakers is essential to mitigate the burden of these neglected parasitic infections and protect both animal and human health.